Pengembangan Rencana Pelaksanaan Pembelajaran Tematik Berbasis Strategi Quantum Learning Tipe Tandur Untuk Madrasah Ibtidaiyah - Santy Afriana; Khoirunisa Khoirunisa; Rif’atul Ajizah; Aninditya Sri Nugraheni Nugraheni (Madania: Jurnal Ilmu-Ilmu Keislaman, 2023)
This research starts from learning materials that are packaged without using learning strategies. The implementation of the quantum learning strategy is more meaningful because it pays attention to the surrounding environment. This study aims to develop a learning plan that is adapted to the steps of the TANDUR-type quantum learning strategy. The subjects in this study found first grade students at MI Normal Islam Rakha. This study uses research and development (RnD) with a 4D model define, design, develop, dessiminate. Feasibility trials at the development stage were carried out by experts and linguists. The results of research by material experts obtained an average percentage score of 87% with a very decent category. Based on the assessment of linguists obtained an average percentage score of 76.5% with a decent category. This shows that the development of thematic learning plans using the TANDUR type of quantum learning strategy is feasible to be used.